The contributing factors affects on special events and shopping venue - Mohamad Hazni Aizal, Hamdan (2015)
The contributing factor effects on special events and shopping venue is intended to determine factors that an event has an impact to the shopping venue. The objective of this study is to investigate the contributing factor that attracts visitor arrivals to special events that complement the shopping venue and to compare the satisfactory level of the visitor to the special events and to the shopping venue. There are five chapters involved in this study. This study is conducted because to know what will happen to the shopping venue with the existence of the special event and the impact. The first chapter describes about the main issue and the problem statement when special event always held close to the shopping mall. In the second chapter relates to the theories and facts related to the special event and shopping venue. Next, for the third chapter, discusses about the way to obtain information. In this study, questionnaires were distributed to 300 randomly selected visitors to. The data obtain will be analyze in the Statistical Package for the Social Sciences (SPSS) software specific to determine the values of the result. In the next chapter, which is fourth chapter is discuss the analysis of data obtained from questionnaires. There are 300 sets of questionnaires were distributed and all can be used for analysis. In this chapter, the analysis offered is the mean, mode, standard deviation and so on. For the final chapter is the fifth chapter. This chapter discuss about finding in the previous chapter to ensure that the entire objective in this study were successfully achieved. These findings also give a warning sign to shopping venue that they are now compete with the special events around them because of decreasing number of visitor go to the shopping venue during a special event.